2007
DOI: 10.1118/1.2712415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsatile blood flow in large vessels on thermal dose distribution during thermal therapy

Abstract: The aim of this study is to evaluate the effect of pulsatile blood flow in thermally significant blood vessels on the thermal lesion region during thermal therapy of tumor. A sinusoidally pulsatile velocity profile for blood flow was employed to simulate the cyclic effect of the heart beat on the blood flow. The evolution of temperature field was governed by the energy transport equation for blood flow together with Pennes' bioheat equation for perfused tissue encircling the blood vessel. The governing equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Bioheat transfer analysis often needs to deal simultaneously with transient and spatial heating inside living tissues. The Pennes bioheat transfer equation [26], which describes the exchange magnitude of the heat transfer between tissue and blood, has been used widely for solving the temperature distribution for thermal therapy [27,28]. We will perform a more detailed analysis by solving the Pennes bioheat transfer equation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Bioheat transfer analysis often needs to deal simultaneously with transient and spatial heating inside living tissues. The Pennes bioheat transfer equation [26], which describes the exchange magnitude of the heat transfer between tissue and blood, has been used widely for solving the temperature distribution for thermal therapy [27,28]. We will perform a more detailed analysis by solving the Pennes bioheat transfer equation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al [7] designed an instrument for measuring the heat convection coefficient on the endothelial surface of arteries. Effects of pulsatile blood flow in arteries during thermal therapy were studied by Craciunescu and Clegg [8] as well as by Horng et al [9]. Shrivastava and Roemer [10] studied heat transfer rate from one blood vessel to another and also that from a blood vessel to tissue.…”
Section: Introductionmentioning
confidence: 99%
“…We assumed an average uniform velocity profile for the blood fluid inside the vessels, as well as fully developed flow. Studies [20,21] have shown insignificant differences between uniform and non-uniform profiles (i.e. pulsating flow) inside the vessels.…”
Section: Mathematical and Numerical Modelingsmentioning
confidence: 97%